2021
DOI: 10.1142/s1793984420300010
|View full text |Cite
|
Sign up to set email alerts
|

Iron Oxide Nanoparticles for Tissue Repair and Regeneration

Abstract: Iron oxides are naturally occurring compounds, and several methods have been developed for generating iron oxide nanoparticles (IONPs) with a focus on precisely modulating their size and physicochemical properties. Facile synthesis approaches, narrow size distribution, ease of surface modification, tunable magnetic properties, and size-dependent elimination from blood circulation, make IONPs attractive for use in different biomedical applications. This review describes the use of IONPs for application in tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…It has also been reported that nanomaterials with POD-like activity can catalyze RXS generation for chemo-driven antibacterial therapy, 340,341 with iron oxide NPs (IONPs) as a typical example of these chemo-driven therapeutic nanomaterials. 341 Due to their POD-like ability, IONPs can react with H 2 O 2 to promote OH production for effective bactericidal effects. Meanwhile, novel semiconductors with different energy bands can also trigger RXS generation under light irradiation, such as in the PDT therapeutic modality.…”
Section: Anti-infectionmentioning
confidence: 99%
“…It has also been reported that nanomaterials with POD-like activity can catalyze RXS generation for chemo-driven antibacterial therapy, 340,341 with iron oxide NPs (IONPs) as a typical example of these chemo-driven therapeutic nanomaterials. 341 Due to their POD-like ability, IONPs can react with H 2 O 2 to promote OH production for effective bactericidal effects. Meanwhile, novel semiconductors with different energy bands can also trigger RXS generation under light irradiation, such as in the PDT therapeutic modality.…”
Section: Anti-infectionmentioning
confidence: 99%
“…Furthermore, previous studies have reported that topically applied iron chelators and their novel therapeutic agents are able to improve the wound healing [32]. Recently, the antibacterial properties of these NPs have been studied in some depth [33,34], such as their application in regenerative medicine and tissue engineering [35], above all for neural and musculoskeletal tissues [36]. Thus, an interesting approach would be the incorporation of Fe 3 O 4 NPs within CS polymeric NPs in order to combine their individual regenerative and antimicrobial properties in one unique element.…”
Section: Introductionmentioning
confidence: 99%